Preparasi dan Karakterisasi Sistem Pembawa Liposom dari Ekstrak Etanol Daun Miana (Coleus atropurpureus L. Benth) - Muhamad Handoyo Sahumena; Suryani Suryani; Widya Pratiwi (Indonesian Journal of Pharmaceutical Education, 2023)
Miana (Coleus atropurpureus L. Benth) is a plant in the ornamental plant group that has benefits for the body. The part of the plant that is efficacious as medicine is on the leaves with a brownish red color. However, extracts from miana leaves are hydrophilic, making it difficult to penetrate biological membranes which are rich in lipids and difficult to use topically. One way to overcome this problem is by making liposome carrier systems. Liposomes are carrier systems consisting of phospholipids and cholesterol with the ability to encapsulate hydrophilic and hydrophobic compounds. Parameters for the success of the liposome formula include vesicle shape, high adsorption efficiency and liposome vesicle size using a particle size analyzer (PSA). The liposome formula was obtained through the thin layer hydration method using phosphatidylcholine and cholesterol. The composition of the optimum liposome formula of miana leaf ethanol extract is 0.2% phosphatidylcholine and 0.4% cholesterol. The optimum formula obtained is a complex spherical structure, efficiency entrapment 92.91%, vesicle size 573.6 nm and polydispersity index is 0,505.